2005
DOI: 10.1590/s0102-311x2005000300004
|View full text |Cite
|
Sign up to set email alerts
|

Validade de constructo de escala de apoio social do Medical Outcomes Study adaptada para o português no Estudo Pró-Saúde

Abstract: This paper evaluates the construct validity of the Medical Outcomes Study's social support scale adapted to Portuguese, when utilized in a cohort study among non-faculty civil servants at a university in Rio de Janeiro, Brazil (Pró-Saúde Study). Baseline data were obtained in 1999, when 4,030 participants (92.0% of those eligible) completed a multidimensional self-administered questionnaire at the workplace. From the original scale's five social support dimensions, factor analysis of the data extracted only th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
155
2
183

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(344 citation statements)
references
References 27 publications
4
155
2
183
Order By: Relevance
“…The majority of the elderly people of this study reported high levels of perceived social support, confirming the data from previous research (16,18) . The perception of having good social relationships with family, and that these relationships can help in times of need, is an important factor in maintaining quality of life for the elderly (12) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The majority of the elderly people of this study reported high levels of perceived social support, confirming the data from previous research (16,18) . The perception of having good social relationships with family, and that these relationships can help in times of need, is an important factor in maintaining quality of life for the elderly (12) .…”
Section: Discussionsupporting
confidence: 90%
“…Considering, however, that data referring to cognitive evaluation had been used in a previous study, which selected its subjects through a sampling procedure, the present study took as its population the total number of elderly persons evaluated in 2007 and who had obtained a MEMS result below the cut-off point according to level of schooling (15) varying from 20 to 100 points, with a higher score indicating a higher level of social support) (16) ; the Katz Index, for assessing performance in basic activities of daily living, which involve activities related to self-care such as feeding oneself, washing, dressing, carrying out personal hygiene and maintaining continence (3) ; the Pfeffer Functional Activities Questionnaire for assessment of performance of instrumental activities of daily living, which include ability to prepare meals, go shopping, use transport, take care of the house, use the telephone, take care of one's finances, take one's medication and remember arrangements, events, family members and holidays (4) . as studies indicate that social support perceived by the elderly is as important as that which is actually received (17) .…”
Section: Introductionmentioning
confidence: 99%
“…Some of these Brazilian experiences have been guided by the proposal of Herdman et al, either totally 39,40,47,51,52 or partially. 1,11,16,[21][22][23]26,45,54,64 …”
Section: Process Of Cross-cultural Adaptationmentioning
confidence: 99%
“…dade de Beck (Beck Anxiety Inventory, BAI) 19 , PTSD Checklist -Civilian Version (PCL-C) 20 , Escala de Experiências Dissociativas (DES) 21 e Escala de Traço de Afeto Negativo (PANAS-N) 22 . Também foram utilizados os seguintes questionários referentes a aspectos positivos: Escala de Traço de Afeto Positivo (PANAS-P) 22 , Escala de Resiliência (ER89) 23 e Escala de Apoio Social do Medical Outcomes Study 24 . Todos os instrumentos foram utilizados em versões previamente validadas para o português.…”
Section: Introductionunclassified